Arthroscopic Repair of the Anterior Talofibular Ligament Produces Good Clinical Outcome Scores Both with and without Inferior Extensor Retinaculum Reinforcement: A Meta-Analysis - Benjamin Murray DO, LT MC USN; Ali Mirghasemi MD; Gene Shaffer MD; James Raphael MD (Foot & Ankle Orthopaedics)
Category: Arthroscopy; Ankle Introduction/Purpose: Arthroscopic techniques for lateral ankle instability generally involve either direct repair solely of the anterior talofibular ligament (ATFL) remnant or repair of the ATFL with inferior extensor retinaculum (IER) reinforcement. Both techniques produce strong clinical outcomes, which questions the necessity of IER reinforcement. Studies comparing arthroscopic lateral ankle ligament stabilization techniques are limited, especially those directly comparing pure ATFL repair to ATFL repair with IER reinforcement. The purpose of this study is to compare clinical outcomes of arthroscopic repair of the ATFL without IER reinforcement to arthroscopic ATFL repair procedures involving IER reinforcement Methods: A meta-analysis per PRISMA guidelines was conducted. Search keywords included arthroscopic, all-inside, ankle stabilization, lateral ankle sprain, anterior talofibular ligament, and lateral ankle instability. To assess the relationship of type of surgical procedure (ATFL repair with versus without IER reinforcement) to reported clinical outcomes based on the American Orthopaedic Foot and Ankle Society (AOFAS) score, the Karlsson and Peterson Scoring System for Ankle Function (KAFS), and the Visual Analogue Score (VAS), we used the standardized mean difference (SMD) with a 95% confidence interval of preoperative to postoperative scores as an effect size. The method of random-effects model was used to calculate the overall summary estimates. Results: 638 studies met the initial search criteria. 34 studies met final inclusion criteria and were included in the meta-analysis. Patients receiving arthroscopic ATFL repair both with and without IER reinforcement had significantly improved pre-operative to post-operative clinical outcome scores. Arthroscopic ATFL repair with IER reinforcement resulted in a significantly higher pre-operative to post-operative SMD for KAFS (p=0.091) and VAS (p=0.065) scores compared to arthroscopic ATFL repair without IER reinforcement. There was no significant difference in the pre-operative to post-operative SMD of AOFAS (p=0.453) scores when comparing surgical procedures. Conclusion: Arthroscopic ATFL repair produces strong clinical outcome scores both with and without IER reinforcement.